\displaystyle y={{\cot }^{2}}x-5+\cos ecx

It is difficult to differentiate cot x and cosec x directly. You need to change to a form where you can differentiate  cot x = \displaystyle \frac{1}{{\tan x}} and cosec x = \displaystyle \frac{1}{{\sin x}}.

\displaystyle y=\frac{1}{{{{{\tan }}^{2}}x}}-5+\frac{1}{{\sin x}}

\displaystyle y={{\tan }^{{-2}}}x-5+{{\sin }^{{-1}}}x

Use chain rule to differentiate the equation. Don’t forget to differentiate tan x to \displaystyle {{\sec }^{2}}x and sin x to \displaystyle \cos x

\displaystyle \frac{{dy}}{{dx}}=-2{{\tan }^{{-3}}}x\times {{\sec }^{2}}x-{{\sin }^{{-2}}}x\times \cos x

\displaystyle \frac{{dy}}{{dx}}=\frac{{-2}}{{{{{\tan }}^{3}}x}}\times \frac{1}{{{{{\cos }}^{2}}x}}-\frac{1}{{{{{\sin }}^{2}}x}}\times \cos x

\displaystyle \frac{{dy}}{{dx}}=\frac{{-2}}{{{{{\tan }}^{3}}x{{{\cos }}^{2}}x}}-\frac{{\cos x}}{{{{{\sin }}^{2}}x}}


Additional Math and Combine Science (Physics/ Chemistry) Tuition at Woodlands, Choa Chu Kang, Yew Tee, Sembawang and Yishun.